Potential for biological control of porina (Wiseana spp) with a novel insecticidal bacterium Yersinia n sp (MH96) EN65 strain - Brownbridge, M.; Ferguson, C.; Saville, D.J.; Swaminathan, J.; Hurst, M.R.H.; Jackson, T.A. (New Zealand Plant Protection, 2008)
Porina (Wiseana spp larvae) are endemic pests of pasture If detected early young larvae can be controlled with diflubenzuron but generally damage is not predicted and organophosphate insecticides (eg diazinon chlorpyrifos chlorfon) are required Yersinia n sp (MH96) cf entomophaga (EN65 strain) a novel bacterium with insecticidal properties is pathogenic to late instar Wiseana spp larvae in laboratory assays and has potential as a biopesticide This trial measured the effect of two formulations of EN65 and a commercial formulation of Bacillus thuringiensis var kurstaki (Btk) against late instar porina EN65 was formulated in a sprayable biopolymer and on to a kibbled wheat bait Both EN65 formulations caused significant mortality of porina larvae and reduced feeding damage on white clover; efficacy was superior to Btk Survival of the bacterium in the sprayable biopolymer formulation was enhanced compared to a nonformulated broth culture Bacterial survival on the kibbled wheat bait was better when stored at 4C compared to 20C over 3 months